Comparison of Clinical Interventions between Student Pharmacists on Advanced Pharmacy Practice Experiences in Indianapolis, Indiana versus Eldoret, Kenya - Rakhi Karwa; Monica L. Miller; Ellen Schellhase; Susie Crowe; Imran Manji; Shelby Albertson; Monica Frauhiger; Sonak Pastakia (MDPI AG, 2023)
Student pharmacists can have a positive impact on patient care. The objective of this research was to compare clinical interventions made by Purdue University College of Pharmacy (PUCOP) student pharmacists completing internal medicine Advanced Pharmacy Practice Experiences (APPE) in Kenya and the US. A retrospective analysis of interventions made by PUCOP student pharmacists participating in either the 8-week global health APPE at Moi Teaching and Referral Hospital (MTRH-Kenya) or the 4-week adult medicine APPE at the Sydney & Lois Eskenazi Hospital (SLEH-US) was completed. Twenty-nine students (94%) documented interventions from the MTRH-Kenya cohort and 23 (82%) from the SLEH-US cohort. The median number of patients cared for per day was similar between the MTRH-Kenya (6.98 patients per day, interquartile range [IQR] = 5.75 to 8.15) and SLEH-US students (6.47 patients per day, IQR = 5.58 to 7.83). MTRH-Kenya students made a median number of 25.44 interventions per day (IQR = 20.80 to 28.95), while SLEH-US students made 14.77 (IQR = 9.80 to 17.72). The most common interventions were medication reconciliation/t-sheet rewrite and patient chart reviews for MTRH-Kenya and the SLEH-US, respectively. This research highlights how student pharmacists, supported in a well-designed, location-appropriate learning environment, can positively impact patient care.